Analysis of risk factors and their predictive efficacy for postoperative gastrointestinal dysfunction in patients with severe traumatic brain injury - Yang, Caiyun; Xu, Chunyang; Wen, Shun; Yu, Sun; Yang, Liang; Pan, Liming; Xu, Feng (Frontiers in Neurology, 2025)
IntroductionTo investigate the risk factors and their warning effectiveness for postoperative gastrointestinal dysfunction in patients with severe traumatic brain injury (sTBI).MethodsA total of 160 patients with sTBI were divided into the gastrointestinal dysfunction group (n = 64) and the non-gastrointestinal dysfunction group (n = 96). Data including gender, age, past medical history, types of intracranial hematoma, injury type, preoperative GCS, postoperative GCS, postoperative intracranial pressure (ICP), operation time, intraoperative blood pressure, enteral nutrition initiation time, APACHE II score, SOFA score, insulin-like growth factor 1 (IGF-1), and fecal calprotectin (FC), were collected. Univariate and multivariate binary logistic regression analyses were conducted. The ROC curve and AUC were plotted to assess the predictive efficacy of each risk factor for gastrointestinal dysfunction.ResultsThe univariate analysis revealed that intraoperative blood pressure, past medical history, postoperative ICP, enteral nutrition initiation time, postoperative GCS score, neuron specific enolase, S100, IGF-1, and FC were significantly associated with the occurrence of gastrointestinal dysfunction. In addition, multivariate binary logistics regression analysis indicated that IGF-1, postoperative ICP, and FC were significantly associated with postoperative gastrointestinal dysfunction. Among these factors, the ROC curve of IGF-1 demonstrated a higher warning efficacy, which was similar to FC, whereas the ROC curve of ICP showed slightly lower AUC.DiscussionIGF-1, postoperative ICP, and FC are independent factors affecting postoperative gastrointestinal dysfunction in patients with sTBI. Notably, IGF-1 and FC exhibit higher predictive efficacy, while postoperative ICP shows a slightly lower predictive efficacy.